Underground Economy: an insight into the World of Tax Havens and Money Laundering - B.V. Kumar (New Delhi Konark Publishers International, 2017)
For any banking institution, financial assets are their life and blood. To attract money away from the developed nations, banks and financial institutions in tax havens necessarily offer least stringent money laundering standards, minimum tax liability and maximum secrecy. As a corollary, this leads to a higher risk of infiltration by criminal organisations that seek financial secrecy to conceal their assets. The banks and fiducial consultants in tax havens assist their clientele through legal instruments such as corporations and trusts. From organised crime to tax havens, this book interlinks the nexus between hidden money, drug trafficking, serious crime and money laundering. The author delves into detailed case studies of banks and financial institutions to unravel the deep roots that cause this scourge. The author also touches upon financial secrecy laws and how they encourage the laundering process.
Keywords: IRS as an author